Management of Gingival Curettage in Stage II Grade A Localized Periodontitis Patients - Nanda Alfarosus Salsabil; Peni Pujiastuti (Health and Technology Journal (HTechJ), 2026)
Periodontitis is a chronic inflammatory disease affecting the supporting structures of the teeth, primarily caused by pathogenic microorganisms. It is characterized by periodontal pocket formation, bleeding on probing (BOP), and clinical attachment loss. This case report describes the comprehensive management of periodontitis, with a focus on gingival curettage as an adjunctive procedure. A 31-year-old female patient presented with complaints of dental plaque accumulation, bleeding gums during tooth brushing, and tooth mobility. The Oral Hygiene Index-Simplified (OHI-S) score was 4.4, indicating poor oral hygiene. Clinical examination revealed erythematous gingiva with a BOP score of 29.2% and probing depths of 4 mm on the labial surfaces of teeth 12, 32, 31, 41, and 42. Grade II mobility was observed in teeth 32, 31, 41, and 42. Radiographic findings showed horizontal bone loss in the coronal third of tooth 12 and vertical bone resorption in teeth 32, 31, 41, and 42. Initial periodontal therapy included oral hygiene instruction and scaling and root planing. At one-week follow-up, persistent periodontal pockets and mobility were noted; therefore, splinting was performed, followed by gingival curettage one week later. The intervention resulted in a reduction in periodontal pocket depth and improvement in clinical parameters. This case highlights the effectiveness of gingival curettage as an adjunct to non-surgical and supportive periodontal therapy in managing moderate periodontitis.